Wildlife poaching - Greene, Laura (New York : Franklin Watts, 1994)
Text and photographs discuss wildlife poaching including the reasons why people poach, the type of animals that are killed, and what is being done to save certain species from extinction.
Includes bibliographical references (p. 137-138) and index.
Appraisal-Science Books for Young People.
Booklist.
Wilson's Senior High School.
Young Adult
Keywords: Poaching -- Juvenile literature; Poaching; Hunting